Genetic and morphological variability among the populations assigned to the genus Tropiocolotes Peters, 1880 (Squamata: Gekkonidae) in south Iran - Rounaqi, Iman; Rastegar-Pouyani, Eskandar; Gholamifard, Ali; Hosseinian, Saeed (Zootaxa, 2017)
Geckos of the genus Tropiocolotes are known from Africa through the Middle East to Iran and currently include ten recognized species. Recently Tropiocolotes naybandensis was described from Iran based on morphological data. Here, we confirm the taxonomic status of this species using both molecular and morphological data, and compare it with other populations of Tropiocolotes from Iran. A distinct new clade with high node support from southern Iran shows high genetic divergence from the clade of T. naybandensis and T. steudneri from Africa. Based on morphological examinations, three meristic characters differentiate the two clades: (1) number of gulars; (2) number of subdigital lamellae under first toe; (3) number of postmental scales. Data from two mtDNA genes (16S rRNA and COI) indicate mean genetic divergences for 16S and COI between T. naybandensis and a population from Bandar-e Lengeh of 3.8% and 6.2%, respectively. In addition, the genetic divergences between these two groups and a sample of T. steudneri from Egypt are 10.8% and 10.1% for 16S and 18% and 16.7% for COI, respectively. We thus confirm the specific status of T. naybandensis and present evidence for the existence of a new species level taxon of Tropiocolotes in south Iran.